1987
DOI: 10.1111/j.1524-4725.1987.tb00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulation of Wound Healing by Lasers: Experimental Approaches in Animal Models and in Fibroblast Cultures

Abstract: Recent evidence suggests that low-energy lasers, such as an He-Ne laser, might stimulate wound healing. In this review we are summarizing our recent observations indicating that low-energy lasers enhance collagen gene expression both in skin fibroblast cultures in vitro, as well as in animal models of wound healing in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
99
0
7

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(108 citation statements)
references
References 14 publications
2
99
0
7
Order By: Relevance
“…Published data indicates that low-power irradiation can enhance DNA synthesis [19], collagen [20] and procollagen production [21,22] as well as increase proliferation rate [23,24] and alter locomotory characteristics in connective tissue cells [25]. These findings are true for skin and embryonal fibroblasts.…”
Section: Introductionsupporting
confidence: 61%
“…Published data indicates that low-power irradiation can enhance DNA synthesis [19], collagen [20] and procollagen production [21,22] as well as increase proliferation rate [23,24] and alter locomotory characteristics in connective tissue cells [25]. These findings are true for skin and embryonal fibroblasts.…”
Section: Introductionsupporting
confidence: 61%
“…LLI therapy reportedly influences soft tissue repair [1] and nerve regeneration [2], and is used in clinical situations such as wound healing, inhibition of plaque formation on teeth, enhanced healing of dental extraction sockets, recovery from nerve injuries, and in treating painful joint disorders [3][4][5][6]. In particular, the effects of LLI on the nervous system suggest that it can block the conduction of nerve impulses [7][8][9] and improve recovery from nerve injuries in both experimental rat models [2,10,11] and clinical investigations [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…When the waveform of the twitch curve is analyzed, the latency (LAT) corresponds to steps (1)-(3), the contraction period (CP) corresponds to step (4), and the relaxation period (RP) corresponds to step (5).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical observations and limited basic research suggest that low energy lasers may biostimulate cutaneous wound healing. In vitro data demonstrate that low level laser irradiation can stimulate cell proliferation [11,12], DNA and RNA synthesis [13], collagen synthesis [13,14], the release of growth factors [15], and keratinocyte migration [16,17]. On the contrary, other in vitro low level laser irradiation studies have reported no biological effect or even bioinhibition [18,19].…”
Section: Introductionmentioning
confidence: 99%